Catalytic purification of fuel oil from hydrogen sulphide and mercaptans - I. V. Pletneva; Yu. A. Gavrilov; E. N. Silkina; I. V. Isichenko (Тонкие химические технологии, 2014)
Increasing environmental regulations according to the content of toxic volatile sulfur impurities in fuel oil requires improvement existing and development of new absorbers and ways of their application. The results of the study of oxidative demercaptanization of model mixtures containing hydrogen sulfide and hydrogen sulfide/ethyl mercaptan in the presence of metal complex catalysts are shown. It is established that the required degree of purification (conversion of hydrogen sulphide) is achieved at a ratio of kt/H2S=1.5, which is much lower than required when using scavenger. Experiments carried out at the refinery of "TAIF-NK" to remove hydrogen sulfide from fuel oil have shown the efficiency close to that obtained in experiments on model compounds. These catalysts are also effective in conversion of light mercaptans of fuel oil. Irreversible nature of transformation of hydrogen sulfide and thiols into nontoxical forms and no negative impact on the properties of the final product of this method is established.